The design and evaluation of a novel low‐cost portable ventilator. (3rd June 2019) - Darwood, A.; McCanny, J.; Kwasnicki, R.; Martin, B.; Jones, P.
Summary: Modern mechanical ventilator technologies broadly consist of digitally‐controlled electronic devices and analogue systems driven by compressed gas sources. Drawbacks such as high cost, complex maintenance and the need for cumbersome sources of compressed driving gas hinder adoption in pre‐hospital and low‐resource environments. We describe the evaluation and testing of a simple, low‐cost alternative ventilator that uses a novel pressure‐sensing approach and control algorithm. This is designed to provide portable positive‐pressure mechanical ventilation at a reduced cost, while autonomously monitoring patient condition and important safety parameters. A prototype ventilator was constructed and evaluated using an anaesthetic test‐lung as a patient surrogate. Using a modifiable test‐lung and digital pressure sensor, we investigated ventilation pressure waveform circuit leak detection, and compliance and resistance change detection. During intermittent positive‐pressure ventilation to the test‐lung, the prototype system showed acceptable pressure waveform parameters: all simulated circuit leaks ≥ 6 mm 2 in size were detected; compliance changes were detected between 10 ml.cmH2 O −1, 20 ml.cmH2 O −1 and 50 ml.cmH2 O −1 ; and resistance changes were detected across the available simulated range. These results show this prototype technology has the potential to provide safe emergency ventilation without the use of any complex digital sensors or software while its construction and design enables significant reductions in cost and complexity. The study suggests further work is now justified in progressing the technology to clinical trials.